Effective fisheries management with few data: a management procedure approach - Geromont, Helena Francine (Department of Mathematics and Applied Mathematics, 2022)
Complex stock assessments which typically rely on a comprehensive set of age or length data are traditionally seen as an essential requirement for sound fisheries management. An alternative process less commonly adopted for the provision of reliable on-going management advice is called the Management Procedure (MP) approach. This approach is pro-active and strategic rather than reactive and tactical, and lends itself well to forecasting and long-term fisheries management. This thesis investigates the application of the MP approach to data-poor as well as data-rich stocks. The majority of fish stocks worldwide are not managed using quantitative analysis as there are not sufficient data on which to base a resource assessment. Often these stocks are relatively ―low-value‖, which renders dedicated scientific management too costly, and a generic approach applicable across a range of stocks is therefore desirable. The aim of the first line of analysis in this thesis is to illustrate the design and testing of some very simple ―off-the-shelf‖ management procedures (MPs) that could be applied to groups of data-poor stocks which share similar key characteristics in terms of demographic parameters. For this initial investigation, a selection of empirical MPs is simulation tested over a wide range of Bayes-like operating models (OMs) representing the underlying dynamics of resources classified as ―depleted‖, in order to ascertain how well these different MPs perform. The moderately data-poor MPs (based on an index of abundance such as provided by a survey or reliable CPUE) perform somewhat better than the extremely data-poor ones (based on the mean length of catch data) as would be expected. Nevertheless the very data-poor MPs perform surprisingly well across the wide range of uncertainty considered for key parameters. The second line of analysis in this thesis focuses on high-value data-rich marine resources: which of the two management paradigms is more suitable where sufficient data for annual stock assessments are readily available? This question is addressed through a retrospective study of management performance over the last twenty years for four North Atlantic fish stocks. The actual assessment advice for these stocks was provided on the basis of complex assessment methods making use of age data. The outcomes are compared to what could have been achieved with much simpler MPs based upon age-aggregated survey indices alone. Even for some of these stocks whose assessments exhibit retrospective patterns, these MPs can achieve virtually equivalent catch and risk performance, with much less inter-annual TAC variability, compared to what actually occurred over the past twenty years. Despite the simplicity of the harvest control rules simulation tested in this thesis, these MPs could well provide the basis to develop generic MPs to manage data-poor stocks, ensuring if not optimal, at least relatively stable sustainable future catches. Moreover, these initial results suggest that simple empirical MPs could provide a defensible, simpler and less costly alternative approach to the provision of scientific management advice for high-value data-rich resources. The advantages of adopting a procedural paradigm for fisheries management purposes are highlighted and rationale is offered as to why it may be prudent (better aligned with the precautionary approach) to adopt an MP approach, even in circumstances where reliable data, expertise and financial support are readily available to perform annual assessments.